2018
DOI: 10.1093/gji/ggy128
|View full text |Cite
|
Sign up to set email alerts
|

Optimized survey design for electrical resistivity tomography: combined optimization of measurement configuration and electrode placement

Abstract: Within geoelectrical imaging, the choice of measurement configurations and electrode locations is known to control the image resolution. Previous work has shown that optimized survey designs can provide a model resolution that is superior to standard survey designs. This paper demonstrates a methodology to optimize resolution within a target area, while limiting the number of required electrodes, thereby selecting optimal electrode locations. This is achieved by extending previous work on the 'Compare-R' algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 46 publications
0
25
0
1
Order By: Relevance
“…Therefore, it is crucial to select a small set of measurements from all possible measurement configurations which can still optimally resolve the underground structure. Successively augmenting a base set of measurements (Wilkinson et al 2006;Stummer et al 2004;Loke et al 2014;Wagner et al 2015;Uhlemann et al 2018), we can employ the iterative update formulae in Eqs. (50) to (52) to quickly compute the model resolution and covariance matrices of the augmented data set.…”
Section: Survey Designmentioning
confidence: 99%
“…Therefore, it is crucial to select a small set of measurements from all possible measurement configurations which can still optimally resolve the underground structure. Successively augmenting a base set of measurements (Wilkinson et al 2006;Stummer et al 2004;Loke et al 2014;Wagner et al 2015;Uhlemann et al 2018), we can employ the iterative update formulae in Eqs. (50) to (52) to quickly compute the model resolution and covariance matrices of the augmented data set.…”
Section: Survey Designmentioning
confidence: 99%
“…Recent developments of the ERT method over the past decade have increased the spatial and temporal resolution for hydrogeological processes monitoring, with optimization of measurement protocols using several hundreds of electrodes (Loke et al, 2014a, 2014b, 2015a, 2015b; Uhlemann et al, 2018; Wilkinson et al, 2012) and with two‐, three‐, and four‐dimensional inversion software (Günther et al, 2006; Johnson et al, 2017, 2010; Rücker et al, 2017, 2006). Moreover, new approaches have been developed to integrate geophysical monitoring results into hydrogeological modeling to complement traditional hydrogeological monitoring techniques for laboratory experiments or field scale studies (Binley et al, 2002; Chou et al, 2016; Dawood et al, 2011; Kemna et al, 2002; Koestel et al, 2008, 2009; Robinson et al, 2009).…”
mentioning
confidence: 99%
“…While subsurface properties were directly related to conductivity in Archie's law (Equation 4), the ability of ERI to resolve the plume depends heavily on the measurement sequence used to generate the ERI data sets. We used a standard dipole‐dipole sequence, which historically has been shown to resolve features at the electrode spacing and depths used here; however, recent advancements and optimizations on a 3D ERI installation (Uhlemann et al ) have shown promise. Optimization of the survey could provide further refinement of the ERI results in a field installation.…”
Section: Discussionmentioning
confidence: 99%